INOKULASI BAKTERI PEREDUKSI KROMIUM HEKSAVALEN SEBAGAI UPAYA BIOREMEDIASI LAHAN PASCA TAMBANG - Fakhriza Akhmad; Fadly H. Yusran; Zuraida Titin Mariana; Badruzsaufari Badruzsaufari (Universitas Lambung Mangkurat, 2011)
The aim of this research was to find out the best combination between the bacteria origin, lime, and organic matter for Cr(VI) reduction. The other objective was to look out the change pattern from Cr(VI) concentration on several period, with hypothesis that bioremediation technology on bacteria, lime, and organic matter combination reduces more Cr(VI) effectively. The results showed that the combination of P.MA origin bacteria with six day period of incubation reduced Cr(IV) for 61,59%. Other, the combination of I.AB origin bacteria with period of 10, 17 and 24 day incubation, reduced Cr(VI) for 76,67, 73,10, and 80,64%, respectively. Analysis of variance for all incubation periods showed significant differences with six and 24 day period were the best treatments. However, a field experiment is needed in order to find the best interaction possible between the origin of the bacteria, lime, and organic matter combination, so that optimum recommendation can be determined for the best possible treatments.